Nuclear factor erythroid 2-related factor 1 regulates the expression of proteasomal genes in ketotic cows and protects mammary cells against free fatty acid–induced endoplasmic reticulum stress - Taiyu Shen; Shijie Xia; Muhammad Usman; Xinyi Xu; Juan J. Loor; Chuang Xu (Journal of Dairy Science)
ABSTRACT: Ketosis is a common metabolic disorder in high-yielding cows and is characterized by high concentrations of BHB and free fatty acids (FFA). High concentrations of FFA induce endoplasmic reticulum (ER) stress in multiple organs including mammary tissue, and result in reduced milk production and lower milk quality. In nonruminants, loss of nuclear factor erythroid 2-related factor 1 (NFE2L1) results in ER stress. The physiological functions and molecular mechanisms controlled by NFE2L1 in bovine mammary tissue are poorly understood. Thus, the present study aimed to elucidate the role of the NFE2L1 on proteasomal homeostasis and ER stress in mammary tissue from early lactation (DIM 6–14) healthy cows (CON, blood concentration of BHB <1.2 mM, n = 10) and cows with clinical ketosis (CK blood concentration of BHB >3 mM, n = 10). Compared with CON, serum concentration of glucose was lower due to CK, while serum concentrations of BHB and FFA were greater. Protein and mRNA abundance of NFE2L1 along with abundance of proteasomal subunits (PSMD1, PSMD14, PSMA1, PSMB1, and PSMB5 genes and PSMB4 and PSMB6 proteins) were lower in cows with CK, indicating that expression of NFE2L1 and proteasomal homeostasis was impaired by ketosis. In vitro, primary bovine mammary epithelial cells were exposed to various concentrations of FFA (0, 0.3, 0.6, or 1.2 mM). Compared with the 0 mM FFA, the ratio of phosphorylated (p)-protein kinase R-like ER kinase (PERK)/PERK along with the expression of inositol-requiring enzyme 1 (IRE1) α, activating transcription factor 6 (ATF6), glucose regulated protein 78 (GRP78), and C/EBP homologous protein (CHOP) was higher with 1.2 mM FFA. A similar response was observed for ER stress-associated genes (CHOP, GRP78, and XBP1) indicating that high concentrations of FFA-induced ER stress. In line with in vivo results, 1.2 mM FFA downregulated the protein and mRNA abundance of NFE2L1, the abundance of PSMB6 protein, and proteasome subunit (PSM) genes (PSMC1, PSMC3, and PSMD1), and increased the accumulation of ubiquitin. This suggested a marked negative effect of high FFA on NFE2L1 and proteasomal homeostasis. Silencing of NFE2L1 triggered upregulation of ER stress-associated genes as well as protein abundance of GRP78 and CHOP. Further, compared with CON-siRNA, the abundance of PSM genes was downregulated in the NFE2L1-siRNA group. In contrast, abundance of markers of ER stress and PSM genes and proteins indicated that overexpression of NFE2L1 relieved the FFA-induced ER stress and improved 26S proteasome homeostasis. Our data suggested that the mammary gland experiences ER stress during ketosis partly due to disruption of proteasomal homeostasis from the excess FFA. As such, NFE2L1 could represent a target for potential therapeutic applications in the field to alleviate the accumulation of malformed proteins that may impair the long-term lactogenic capacity of the udder.